Dowry Using Cultivated Products of Harato Pusako Tinggi: A Case Study in Manggopoh, Agam, West Sumatera - Ilda Yulia Putri; Mesraini Mesraini (JURNAL ILMU SYARIAH, 2025)
The research results show that cases of dowry payments using high proceeds from harato pusako tinggi in the Luhak Agam area, especially in Manggopoh. The highest use of harato pusako tinggi in Manggopoh is only in the form of cultivation results from harato pusako land, such as rice fields and plantations. Harato pusako tinggi in this case still belongs to the clan (kaum). Traditionally, in this case there is no problem, according to the results of interviews with traditional leaders, if emergency conditions are permitted by customary law to cover the shame of the community and family. According to Islamic law, the use of assets resulting from the cultivation of harato pusako tinggi is by Islamic law because the conditions for the validity of the dowry are fulfilled, namely private property (milk al-tam). Previously, community-owned harato pusako had been turned into private property through community permission. It contains hifzh al-nasab (protecting the family) because maintaining the kaum's good name in Islamic law is the same as maintaining the honour and good name of the family. Moreover, in it, there is hifzh al-mal (protecting assets), where the giving of harato pusako tinggi in Manggopoh does not take the form of giving lands such as rice fields and plantations. However, what is given is in the form of harvests from land cultivated and managed from harato pusako tinggi. Keywords: Dowry, Harato Pusako Tinggi, West Sumatera